2021
DOI: 10.1186/s11658-021-00282-9
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs as the critical regulators of doxorubicin resistance in tumor cells

Abstract: Resistance against conventional chemotherapeutic agents is one of the main reasons for tumor relapse and poor clinical outcomes in cancer patients. Various mechanisms are associated with drug resistance, including drug efflux, cell cycle, DNA repair and apoptosis. Doxorubicin (DOX) is a widely used first-line anti-cancer drug that functions as a DNA topoisomerase II inhibitor. However, DOX resistance has emerged as a large hurdle in efficient tumor therapy. Furthermore, despite its wide clinical application, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 218 publications
0
23
0
Order By: Relevance
“…Therefore, targeting tumor cells with a single agent may not lead to a favorable response [ 6 8 ]. Increased drug efflux, changes in the target of drugs, apoptosis, and repair signaling pathways are other mechanisms involved in the resistance of cancer cells to chemotherapeutic drugs [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, targeting tumor cells with a single agent may not lead to a favorable response [ 6 8 ]. Increased drug efflux, changes in the target of drugs, apoptosis, and repair signaling pathways are other mechanisms involved in the resistance of cancer cells to chemotherapeutic drugs [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 51 Besides, the cell cycle participates in the mechanism of drug resistance of tumors, which suggest a potential therapeutic value. 52 The AKT activation might account for the cell invasion and metastasis of HNSC. Studies have demonstrated that PI3K inhibitors represent a therapeutic strategy against HNSC.…”
Section: Discussionmentioning
confidence: 99%
“…The first group includes pharmacological and physiological factors, and the second group includes cell-/tissue-specific factors [24,25]. Increasing the activity of drug efflux pumps such as ATP-binding cassette (ABC), drug detoxification enhancement, DNA repair ability enhancement, epigenetic effects, disruption in cellular signaling pathways, attenuation of apoptosis, and epithelial-mesenchymal transition (EMT) enhancement are among the most important of these mechanisms [22,[26][27][28][29]. Each of these mechanisms, independently or in combination, reduces the therapeutic effect of prescribed drugs and makes cancer treatment more difficult.…”
Section: Drug Resistance: a Major Barrier In Cancer Treatmentmentioning
confidence: 99%